Satan's flying machines: Ellen White and airplanes. - Korpman, Matthew J.
As a prophetic theologian and one of the three historic founders of the Seventhday Adventist Church, Ellen G. White is known for many things. But her opinion about the invention of the airplane is both unknown and fascinating. In fact, until this article, the topic has never been publicly discussed.